Training vs. Rehabilitation - Ebberts, R. (Track Coach, 2021)
The athlete in a rehabilitative state has a different goal, one of return. Rehab is classically defined as a return to a normal state for someone who has been ill or injured. It bears emphasis that one is returning to the "normal" state. While normal might not necessarily be pain free it would be without the movement restrictions of being injured. In a rehabilitative state the weekly or monthly training cycles geared towards improvements are put on hold.